ANALISIS KINERJA REKSADANA SAHAM KONVENSIONAL DAN REKSADANA SAHAM SYARIAH DENGAN MENGGUNAKAN METODE SHARPE - Kusumawati, Rahayu (Polytechnic of State Finance STAN, 2016)
The performance of an investment instrument is measured by the rate of return and risk resulted from the instrument itself. With higher expected rate of return, it is not impossible that the risk which will be created also as high as the rate of the return. Therefore, to minimize the worst possibility, investors are expected to monitor the performance of financial instruments to be chosen. Based on the research, it can be concluded that the level of performance of conventional stock mutual funds with sharia equity funds in Indonesia is still dependent on the desire of investors to get returns. Thus, by using the method of Sharpe, measurement of risk and rate of return better reflect the real situation on an investment.